COMPARISON BETWEEN TEST METHODS TO DETERMINE WOOD EMBEDMENT STRENGTH PARALLEL TO THE GRAIN - Almeida,Diego Henrique de (2016)
ABSTRACT This study compares the test methods according to the ABNT NBR 7190:1997, EN 383:2007, ASTM D5764:2007, EUROCODE 5:2004, NDS:2001 standards in order to provide support to establish a new test method for determining the embedment strength of wood parallel to the grain. Parallel-to-grain tests were carried out for six wood species (Schizolobium amazonicum; Pinus elliottii; Pinus oocarpa; Hymenaea spp.; Lyptus(r): hybrid Eucalyptus grandis and Eucalyptus urophylla, and Goupia glabra) using four diameters (8 mm, 10 mm, 12 mm and 16 mm) for the metal pin fasteners (bolts). The experimental results obtained according to the EN 383:2007 standard were closer to the specific values for the metal-dowel connections design used by ABNT NBR 7190:1997, which are considered equal compression parallel to the grain. The use of maximum embedment force or the force causing displacement of 5 mm between the bolt and the test-piece as criteria for determining embedment strength for EN 383:2007 appears to be more appropriate than the criteria used by the Brazilian and American Standards.